ANALISA KADAR CO DAN NO2 DI UDARA DAN KELUHAN GANGGUAN SALURAN PERNAPASAN PADA PEDAGANG KAKI LIMA DI PASAR SANGKUMPAL BONANG KOTA PADANGSIDIMPUAN TAHUN 2013 - Marlina Sari; devi nuraini santi; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
Analysis the levels of carbon monoxide (CO) and nitrogen dioxide (NO2) in the air and respiratory disturbance cadger in the market Sangkumpal Bonang Padangsidimpuan city in 2013. The market is a public place where there is a process of buying and selling between sellers and buyers. Sangkumpal bonang market is one of the traditional markets are located in the Padangsidimpuan city. The activity of cadger who trade on the sidewalk and the street market can lead to cadger exposed by the pollutants. This is caused by transportation activities which may result in respiratory tract disturbance. This research aims to know the levels of carbon monoxide (CO) and nitrogen dioxide (NO2) in the air and respiratory disturbances at cadger in the market Sangkumpal Bonang Padangsidimpuan city in 2013. This type of research is descriptive. The sample in this research 67 people with using proportional stratified random sampling. The results showed that the majority of respondents aged 41-50 years (38.3%), Most were female gender (67.2%), education level is senior high school (38.8%), respondents who smoked (49.3%), respondents have been trading for ≤ 10 years (49.3%) and have been trading hours of respondents > 8 hours per day (55.2%). Based on the measurement results, the highest point on the front is 18 323 μg/Nm3 for CO and 85.10 μg/Nm3 for NO2. A total of 26 cadger who have complaints of respiratory tract disturbance. The conclusion from this study is that the levels of CO and NO2 around Sangkumpal Bonang market has not exceeded the quality standard. It is recommended to Governments to create policies that govern about the trade cadger in order to avoid exposure to CO and NO2 resulting from transportation activities which could lead to the occurrence of respiratory tract disturbances. Keywords: market, levels of CO and NO2, respiratory tract disturbance